PERLINDUNGAN HUKUM BAGI PENERIMA PINJAMAN BERBASIS ONLINE (PEER TO PEER LENDING) DALAM TRANSAKSI PINJAM MEMINJAM UANG - IBRAHIM, ERNI R. (Ganec Swara, 2025)
This research discusses the legal protection for loan recipients in the growing peer to peer lending (P2P lending) system in Indonesia. Although P2P lending offers innovations in financial transactions, such as convenience and speed, there are various legal risks faced by users of this service. This research identifies three main issues: the mechanism of lending and borrowing in P2P lending, the form of legal protection for lenders when the loan recipient defaults, and the protection of the personal data of the loan recipient.Through an empirical juridical approach, this research finds that legal protection can be done preventively and repressively. Preventive protection includes the organizer’s efforts to ensure that all transactions comply with existing regulations, while repressive protection focuses on the settlement mechanisms that can be accessed by debtors in case of problems with the organizer, especially if the organizer is not registered with the Financial Services Authority (OJK). This research emphasizes the importance of users’ awareness of the risks and their rights in P2P lending transactions to avoid fraudulent practices and violations of the law.